Theoretical aspects in multi-level security management of the European Union in the framework of Security Sector Reform (SSR) - Luiza Wojnicz (Przegląd Europejski, 2020)
Governance is a way for society to get organised, take and implement decisions by means of mutual understanding, reaching agreements and taking actions. It works at every level and is visible in social, political and economic dimensions. It includes a range of instruments, principles, institutions and practical action. States, governmental and non-governmental entities with some competences in governance aim to boost development level and provide security to their citizens. The concept of multi-level governance (MLG) is a characteristic of the European Union (EU) and its areas, where it is capable of exercising its governance at many levels using sectorial internal and external policies. This article focuses on multi-level security management by the European Union within the concept of Security Sector Reform (SSR), dedicated to two sectorial external policies, i.e. the Common Foreign and Security Policy (CFSP), and the Common Security and Defence Policy (CFDP). In this article, the author will attempt to explain what Security Sector Reform actually means for the European Union. For better understanding this analysis author adopted the multi-level governance theory to demonstrate how the SSR concept can be combined with MLG. The author put forward a thesis that, due to many similarities, i.e. in the EU approach to security management in external relations